HYCO-3, a dual CO-releaser/Nrf2 activator, reduces tissue inflammation in mice challenged with lipopolysaccharide - Roberto Motterlini; Aniket Nikam; Sylvie Manin; Anthony Ollivier; Jayne Louise Wilson; Sabrina Djouadi; Lucie Muchova; Thierry Martens; Michael Rivard; Roberta Foresti (Redox Biology, 2019)
Oxidative stress and inflammation are predominant features of several chronic diseases. The nuclear factor erythroid 2-related factor 2 (Nrf2) is a major arbiter in counteracting these insults via up-regulation of several defensive proteins, including heme oxygenase-1 (HO-1). HO-1-derived carbon monoxide (CO) exhibits anti-inflammatory actions and can be delivered to tissues by CO-releasing agents. In this study we assessed the pharmacological and anti-inflammatory properties of HYCO-3, a dual activity compound obtained by conjugating analogues of the CO-releasing molecule CORM-401 and dimethyl fumarate (DMF), an immunomodulatory drug known to activate Nrf2. HYCO-3 induced Nrf2-dependent genes and delivered CO to cells in vitro and tissues in vivo, confirming that the two expected pharmacological properties of this agent are achieved. In mice challenged with lipopolysaccharide, orally administered HYCO-3 reduced the mRNA levels of pro-inflammatory markers (TNF-α, IL-1β and IL-6) while increasing the expression of the anti-inflammatory genes ARG1 and IL-10 in brain, liver, lung and heart. In contrast, DMF or CORM-401 alone or their combination decreased the expression of pro-inflammatory genes but had limited influence on anti-inflammatory markers. Furthermore, HYCO-3 diminished TNF-α and IL-1β in brain and liver but not in lung and heart of Nrf2-/- mice, indicating that the CO-releasing part of this hybrid contributes to reduction of pro-inflammation and that this effect is organ-specific. These data demonstrate that the dual activity of HYCO-3 results in enhanced efficacy compared to the parent compounds indicating the potential exploitation of hybrid compounds in the development of effective anti-inflammatory therapies. Keywords: Carbon monoxide (CO), Nrf2 activators, Dual-activity molecules, Inflammation, Macrophage phenotype